Some microwave properties of lithium-nickel-zinc (lnz) ferrites thermoplastic natural rubber (tpnr) composites / A. H. Siti Atkah … [et al.] - A. H., Siti Atkah; Mustaffa, H. A.; Sahrim, H. A.; Abdul Aziz, M. (2002)
A microwave (Lio.5Feo.5)o.4Nio.3Zno.3Fe204 (LNZ) ferrite was prepared by a conventional sintering method in air. A thermoplastic natural rubber (TPNR) was prepared from polypropylene (PP), natural rubber (NR) and liquid natural rubber (LNR) in the ratio of 70: 20: 10 by melt blending technique. LNZ ferrite -TPNR magnetic composites with 0 - 30 weight percent of ferrite filler were prepared via a Brabender plasticorder internal mixer. The microwave complex scattering parameters due to reflection (S11 *) and transmission (S21 *) were measured using a microwave vector analyzer (MVNA). The microwave reflection, transmission and absorption characteristics of the pure LNZ, pure TPNR and their composites in the frequency range of 0.3 - 13.5 GHz were evaluated and discussed. The results indicate that the composites having higher filler loading can be used for some microwave application.